2021
DOI: 10.3389/fmed.2020.615858
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Profiles and Microbial-Based Therapies in Post-operative Crohn's Disease: A Systematic Review

Abstract: Background and Aims: Gut microbiota recolonization after intestinal resection had been reported to be associated with post-operative recurrence in Crohn's disease (CD). However, the results of different studies are inconsistent and even contradictory. In addition, knowledge on the efficacy of microbial-based therapies in preventing post-operative recurrence of CD is limited. Therefore, the aim of this review was to investigate gut microbiota profiles in patients with CD before and after surgery and evaluate mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…To what extent these lasting immune effects are captured, however, remains unknown. For instance, antimicrobial antibody responses in patients with a history of ileocecal resection corresponded well to typical shifts of bacterial populations that are known to occur following postoperative microbial recolonization in patients with CD (Machiels et al, 2020; Zhuang et al, 2021). Similarly, patients who underwent colon resections in the past showed decreased antibody responses against EBV, whose presence is associated with severe, refractory colitis and a higher colectomy requirement in patients with UC (Hosomi et al, 2018; Pezhouh et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…To what extent these lasting immune effects are captured, however, remains unknown. For instance, antimicrobial antibody responses in patients with a history of ileocecal resection corresponded well to typical shifts of bacterial populations that are known to occur following postoperative microbial recolonization in patients with CD (Machiels et al, 2020; Zhuang et al, 2021). Similarly, patients who underwent colon resections in the past showed decreased antibody responses against EBV, whose presence is associated with severe, refractory colitis and a higher colectomy requirement in patients with UC (Hosomi et al, 2018; Pezhouh et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…Earlier studies had shown that Lachnoclostridium bacteria are generally increased in patients with (complicated) CD, e.g. postoperative CD [61], ASCA-positive CD [62] and active granulomatous colitis [63]. Recently, Lachnoclostridium was also associated with non-invasive diagnosis of colorectal adenoma and colorectal cancer [64, 65].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, there has been interest in the interaction of the gut microbiome after intestinal resection and postoperative recurrence.. 20–22 A recent systematic review failed to draw unambiguous conclusions after evaluating studies on gut microbiota profiles, postoperative recurrence and postoperative microbial-based therapies in CD patients. 23 Some studies reported that postoperative treatment with low-dose metronidazole resulted in decreased postoperative endoscopic recurrence. 24–26 It can be hypothesized that the inverted stapled anastomosis with an open wound and ischaemia provides an excellent entry point for the microbiome, which might interfere with, and potentially complicate, wound healing and gut immunity.…”
Section: Discussionmentioning
confidence: 99%